Reduplikasi dalam Bahasa Jawa: Pola, Fungsi, dan Maknanya (Tinjauan Morfologi) - Pramudya Dhana Bhrata; Agus Hari Wibowo (Journal on Education, 2024)
This research aims to classify the use of Javanese reduplication in words that are widely used by Javanese people in particular through word formation analysis (dwipurwa; dwilingga; dwiwasana) and the function of Javanese reduplication for the people/population in Java, of course. This research study uses a qualitative descriptive method. Therefore, this research specifically analyzes word formation in Javanese reduplication/word repetition/reduplication using the criteria/types of Javanese reduplication (dwipurwa; dwilingga; dwiwasana). The data in this research are words/reduplications in Javanese. The data source in this research is Javanese language society/culture. Supporting sources for this research are relevant articles and journals regarding language reduplication. Data was collected using critical analysis techniques, reading techniques, and continued with note-taking techniques. The data analysis technique used to obtain data is through three stages, namely data reduction, data presentation, and drawing conclusions. The results of this research can be concluded that there are 40 data in total, each of which is divided into 10 data according to the Javanese language reduplication category. The function of Javanese reduplication, for example, is for emphasis, expressivity, aesthetics, etc